Organ Donor Management: Part 1. Toward a Consensus to Guide Anesthesia Services During Donation After Brain Death. (June 2018) - Souter, Michael J.; Eidbo, E.; Findlay, James Y.; Lebovitz, Daniel J.; Moguilevitch, Marina; Neidlinger, Nikole A.; Wagener, Gerhard; Paramesh, Anil S.; Niemann, Claus U.; Roberts, Pamela R.; Pretto, Ernesto A.
Worldwide 715 482 patients have received a lifesaving organ transplant since 1988. During this time, there have been advances in donor management and in the perioperative care of the organ transplant recipient, resulting in marked improvements in long-term survival. Although the number of organs recovered has increased year after year, a greater demand has produced a critical organ shortage. The majority of organs are from deceased donors; however, some are not suitable for transplantation. Some of this loss is due to management of the donor. Improved donor care may increase the number of available organs and help close the existing gap in supply and demand. In order to address this concern, The Organ Donation and Transplantation Alliance, the Association of Organ Procurement Organizations, and the Transplant and Critical Care Committees of the American Society of Anesthesiologists have formulated evidence-based guidelines, which include a call for greater involvement and oversight by anesthesiologists and critical care specialists, as well as uniform reporting of data during organ procurement and recovery.